Synthetic method and application of Bi2SiO5 / g-C3N5 composite material

By loading g-C3N5 onto Bi2SiO5, the Bi2SiO5/g-C3N5 composite material is formed, which solves the problem of low solar energy utilization efficiency of Bi2SiO5 photocatalyst, achieves efficient visible light degradation of organic dyes, and significantly improves the degradation efficiency and rate. .

CN119327501AActive Publication Date: 2025-01-21TARIM UNIV

Patent Information

Application Number
CN202411451338.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

As a photocatalyst, Bi2SiO5 has rapid recombination and recombination of photogenerated electron-hole pairs, which limits its full utilization of solar energy and leads to its degradation performance.

Method used

By loading g-C3N5 onto Bi2SiO5, a Bi2SiO5/g-C3N5 composite material is formed, which combines their respective advantages to improve the overall catalytic efficiency under visible light and more effectively utilize visible light to degrade organic dyes.

Benefits of technology

The degradation efficiency of rhodamine B reached 99.82%, and the degradation rate was 6.02 times and 13.37 times that of g-C3N5 and Bi2SiO5 respectively, and the degradation effect of the composite material was still significant after five repeated experiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327501A_ABST
    Figure CN119327501A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method and application of a Bi2SiO5 / g-C3N5 composite material, a sodium silicate solution is added into a bismuth salt solution, pH is adjusted to be alkaline, a hydrothermal reaction is performed, and after the hydrothermal reaction, filtering, washing, drying and stoving are performed to obtain Bi2SiO5; the preparation method comprises the following steps: carrying out thermal decomposition on 3-amino-1, 2, 4-triazole to prepare g-C3N5; the preparation method comprises the following steps: mixing Bi2SiO5, hexadecyl trimethyl ammonium bromide (CTAB), ethylene glycol and g-C3N5 to obtain a mixed solution, adding Bi2SiO5 into the mixed solution, uniformly stirring, and carrying out a hydrothermal reaction to obtain the Bi2SiO5 / g-C3N5 composite material catalyst. Bi2SiO5-g-C3N5 is prepared by using a hydrothermal method, an organic pollutant solution is degraded under light irradiation, and the degradation capability of the Bi2SiO5-g-C3N5 is tested. Results prove that the active sites, the absorption spectrum, the specific surface area and the catalytic ability of the composite material are all improved under the combined action of holes and heterojunctions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of photocatalytic materials, and more specifically to a synthesis method and application of a Bi2SiO5 / g-C3N5 composite material. Background Art

[0002] With the increasing influence of human activities, energy shortage and environmental pollution have become two major problems that plague the world. The rapid development of industry has also brought about water resource problems. The industrial wastewater discharged by the textile industry, manufacturing industry, printing industry, petroleum industry, etc. contains a large amount of organic pollutants. These organic pollutants contain a large amount of dyes, antibiotics and other carcinogens, which cause water pollution. Among them, the organic dyes produced by textile, leather making, and printing are highly toxic, mutagenic, carcinogenic, and will also pollute the entire ecological environment with the water cycle, which makes the society and the government have to pay attention to this problem. With the continuous exploration and efforts of researchers, there are many ways to purify water pollution, including physical precipitation, biological control, electrochemical method, chemical adsorption, photocatalysis, etc. Physical precipitation and biological control methods take a long time, while chemical adsorption and electrochemical methods are relatively expensive. Among them, photocatalysis is increasingly attracting the attention of society and the government. Photocatalysis is a widely used environmentally friendly technology that can use clean energy (sunlight) to convert organic pollutants into harmless or less harmful substances.

[0003] With the continuous exploration of researchers, the research progress of photocatalytic degradation has begun to take shape. The discovery of new photocatalysts is the key to photocatalysis. Today's photocatalytic semiconductor materials include ZnO, TiO2, CdS, Cu2S, BiOCl, BiOBr, WO3, etc. These semiconductors have different disadvantages and advantages, but the discovery of these semiconductors provides valuable experience and ideas for our research. Niu Zhicheng et al. used bismuth nitrate, sodium silicate and urea as raw materials, and prepared the composite photocatalytic material g-C3N4 / Bi2SiO5 by hydrothermal synthesis and auxiliary high-temperature sintering. The X-ray diffraction spectrum and solid UV-visible diffuse reflectance spectrum were used for characterization. The experimental results show that the photocatalytic degradation activity of the composite catalyst for rhodamine B is significantly higher than that of a single g-C3N4 or Bi2SiO5, the photocatalytic rate reaches 100% in 90 minutes, and it has good stability and reusability. Based on the similarities between Bi2SiO5 and BiOBr in structural composition and morphology and the differences in solubility, Zhu Yongfa et al. used BiOBr with higher solubility as a sacrificial template and introduced new species to cause ion exchange reactions, ultimately resulting in partial or complete conversion of BiOBr into Bi2SiO5 along the thermodynamically permitted direction. They successfully prepared oxygen-rich BiOBr / Bi2SiO5 heterojunction structures and Bi2SiO5 nanoheterojunction flower-like microsphere structures with significantly broadened spectral response range and greatly improved photocatalytic properties.

[0004] Wang et al. reported the preparation of a new type of mesoporous rod-shaped nitrogen-rich nitride (RN-g-C3N5) using 3-amino-1,2,4-triazole as a precursor and green potassium bromide as a template. The mesoporous rod-shaped structure is conducive to the absorption of visible light and the increase of surface area. This special structure and high N content give RN-g-C3N5 a narrow band gap (1.90 eV) and significantly superior photocatalytic performance. In addition, this method is simple to operate, low cost and environmentally friendly. Bai Jinglei et al. prepared Bi / g-C3N5 composite photocatalytic materials by calcination. Compared with pure g-C3N5, the degradation efficiency of MB by 1% Bi / g-C3N5 composite materials was increased by nearly 40%. Yin et al. successfully synthesized Ag3PO4 / g-C3N5 nanocomposites by in-situ precipitation method. It has efficient photocatalytic performance for the degradation of tetracycline hydrochloride, and the removal rate of TCH can reach 90.5%. The results show that the formed Z-type heterojunction promotes the spatial separation of photoinduced charge carriers.

[0005] As an organic semiconductor, graphitized carbon nitride (CNs) has a stable structure and good photocatalytic performance. Among them, nitrogen-rich g-C3N5 has a small band gap (band gap value of 1.70e V) and excellent effect ability on visible light, showing great potential in the field of photocatalysis. It has the characteristics of small band gap and high response to sunlight, but due to its low electron-hole separation rate and low charge mobility, it cannot be used as an excellent photocatalyst. Bi-based semiconductor photocatalysts have a unique electronic band structure and an adjustable and expandable spectral response range, and are considered to be a type of low-toxic, high-efficiency and practical photocatalyst. Among them, Bi2SiO5 semiconductor has good degradation performance. As a promising photocatalyst, Bi2SiO5 has broad practical application prospects. However, due to the rapid recombination of its photogenerated electron-hole pairs, it limits its full utilization of solar energy, so upgrading and transformation of Bi2SiO5 is essential. Summary of the invention

[0006] To this end, the technical problem to be solved by the present invention is to provide a synthesis method and use of a Bi2SiO5 / g-C3N5 composite material. By loading g-C3N5 onto Bi2SiO5, the advantages of each are combined to improve the overall catalytic efficiency under visible light, and to more effectively utilize visible light to degrade organic dyes. The combination of the two increases the range of light response, increases the photocatalytic reaction rate, and the formation of holes enables it to more stably transmit electrons.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] The synthesis method of Bi2SiO5 / g-C3N5 composite material comprises the following steps:

[0009] (1) adding bismuth salt, deionized water and hexadecyltrimethylammonium bromide into a reaction container respectively, and obtaining a mixture after ultrasonic treatment, which is recorded as liquid a;

[0010] (2) adding silicate, deionized water and hexadecyltrimethylammonium bromide into a reaction container respectively, and stirring to obtain a mixture, which is recorded as liquid B;

[0011] (3) adding 3-amino-1,2,4-triazole and deionized water into a reaction container respectively, and stirring to obtain a mixture, which is marked as liquid C;

[0012] (4) First, liquid a and liquid b are mixed and reacted to prepare Bi2SiO5, then liquid c is used to prepare g-C3N5, and finally Bi2SiO5 and g-C3N5 are reacted to prepare Bi2SiO5 / g-C3N5 composite material; or liquid a, liquid b and liquid c are directly mixed and reacted to prepare Bi2SiO5 / g-C3N5 composite material.

[0013] In the synthesis method of the Bi2SiO5 / g-C3N5 composite material, in step (1), the preparation method of liquid a is: adding bismuth nitrate pentahydrate, deionized water, and hexadecyltrimethylammonium bromide (CTAB) into a beaker, covering it with plastic wrap, and performing constant temperature ultrasound to obtain liquid a;

[0014] In step (2), the preparation method of liquid B is: sodium silicate nonahydrate, deionized water and cetyltrimethylammonium bromide (CTAB) are mixed and stirred evenly to obtain liquid B.

[0015] The synthesis method of the Bi2SiO5 / g-C3N5 composite material, in step (1), the preparation method of liquid a is: add 1.94g of bismuth nitrate pentahydrate, 10mL of deionized water and 0.05g of hexadecyltrimethylammonium bromide CTAB into a beaker, cover with plastic wrap, and perform constant temperature ultrasonic treatment for 30min to obtain liquid a;

[0016] In step (2), the preparation method of liquid b is as follows: 0.57 g of sodium silicate nonahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) are mixed and stirred evenly to obtain liquid b.

[0017] The synthesis method of the Bi2SiO5 / g-C3N5 composite material is as follows: liquid b is slowly added to liquid a, the pH of the solution is adjusted with a NaOH solution, and after the reaction is complete, a plastic wrap is covered, and the mixture is stirred at a constant temperature to obtain a milky white suspension;

[0018] The milky white suspension was transferred to a polytetrafluoroethylene reactor, reacted at high temperature, naturally cooled to room temperature, filtered under reduced pressure, washed three times with anhydrous ethanol and deionized water respectively, and then dried. The dried material was poured into a clean mortar and ground to obtain white Bi2SiO5 material.

[0019] The synthesis method of the Bi2SiO5 / g-C3N5 composite material is as follows: liquid b is slowly added to liquid a, and the pH of the solution is adjusted to 10.0 with a 2 mol / L NaOH solution. After the reaction is complete, the solution is covered with a plastic wrap and stirred at a constant temperature for 30 mL to obtain a milky white suspension.

[0020] The milky white suspension was transferred to a polytetrafluoroethylene reactor, reacted at 120°C for 12 hours, naturally cooled to room temperature, filtered under reduced pressure, washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 8 hours. The dried material was poured into a clean mortar and ground to obtain white Bi2SiO5 material.

[0021] The synthesis method of the above-mentioned Bi2SiO5 / g-C3N5 composite material is as follows: 3-amino-1,2,4-triazole and deionized water are placed in a beaker, stirred to fully dissolve them, and then the beaker is transferred to a constant temperature heating magnetic stirrer. After the solution in the beaker is evaporated to dryness, it is transferred to a tubular furnace for heating reaction. After the tubular furnace is cooled to room temperature, the porcelain boat is taken out, the material is poured into a mortar and fully ground, and the obtained material is pure g-C3N5.

[0022] The synthesis method of the above-mentioned Bi2SiO5 / g-C3N5 composite material is as follows: 1.5 g of 3-amino-1,2,4-triazole and 30 mL of deionized water are placed in a beaker, stirred to fully dissolve, and then the beaker is transferred to a constant temperature heating magnetic stirrer at a heating temperature of 80°C. After the solution in the beaker is evaporated to dryness, it is transferred to a tubular furnace and heated to 520°C at 5°C / min, and kept at 520°C for 3 hours. After the tubular furnace is cooled to room temperature, the porcelain boat is taken out, the material is poured into a mortar and fully ground, and the obtained material is pure g-C3N5.

[0023] The synthesis method of the Bi2SiO5 / g-C3N5 composite material is as follows: cetyltrimethylammonium bromide (CTAB), ethylene glycol and g-C3N5 are added to a beaker, and then transferred to an ultrasonic instrument and subjected to constant temperature ultrasonication to obtain a mixed solution;

[0024] Then Bi2SiO5 was added to the mixed solution, and after continued constant temperature ultrasound, it was transferred to a magnetic stirrer. After constant temperature and vigorous stirring, it was transferred to a polytetrafluoroethylene reactor for hydrothermal reaction. After the reactor was naturally cooled to room temperature, it was filtered, washed with methanol and deionized water, and dried to obtain a Bi2SiO5 / g-C3N5 composite material.

[0025] The synthesis method of the above-mentioned Bi2SiO5 / g-C3N5 composite material is as follows: liquid c is slowly added to liquid b, and after stirring evenly, the liquid c is slowly added to liquid a, and the mixture is stirred evenly, and the pH of the mixed solution is adjusted to alkaline with a NaOH solution. After the reaction is complete, a suspension is obtained after stirring, and the suspension is recorded as liquid d; liquid d is transferred to a polytetrafluoroethylene reactor for hydrothermal reaction, and then the obtained mixture is evaporated to dryness, and the solid obtained after evaporation is ground to obtain a composite material precursor; the composite material precursor is transferred to a tubular furnace for heating and reaction, and after the tubular furnace is cooled to room temperature after the reaction, it is taken out and ground to obtain the Bi2SiO5 / g-C3N5 composite material.

[0026] The use of Bi2SiO5-g-C3N5 composite material, the above-mentioned Bi2SiO5 / g-C3N5 composite material is used for photocatalytic degradation of organic pollutants.

[0027] The technical solution of the present invention achieves the following beneficial technical effects:

[0028] The degradation efficiency of the composite material Bi2SiO5 / g-C3N5 with a doping ratio of Bi2SiO5:g-C3N5=1:10% for rhodamine B reached 99.82%, and its degradation rates were 6.02 times and 13.37 times of g-C3N5 and Bi2SiO5 respectively. After five repeated experiments, the degradation effect of the composite material can still reach 89.93%. This shows that Bi2SiO5 and g-C3N5 synergistically enhance the material's ability to absorb visible light, promote the generation of photogenerated electrons-holes, thereby improving the photocatalytic reaction activity and accelerating the photocatalytic degradation rate.

[0029] Bi2SiO5 / g-C3N5 was prepared by hydrothermal method, and then degraded Rhodamine B (RhB) solution under sunlight simulated by 500W xenon lamp to test its degradation ability. The results show that under the joint action of holes and heterojunction, the active sites, absorption spectrum, specific surface area and catalytic ability of the composite material are improved.

[0030] The higher the separation efficiency of photogenerated electron-hole pairs, the longer the lifetime and the longer the time they participate in the reaction. Therefore, the photocatalytic performance is mainly determined by the recombination rate or lifetime of the photogenerated electron-hole pairs. The low intensity of the photoluminescence spectrum of the Bi2SiO5 / g-C3N5 composite material prepared in this application indicates that its electron-hole pair recombination rate is lower, the separation efficiency of photogenerated carriers is higher, and the time they participate in the reaction is longer, thus having higher photocatalytic activity.

[0031] During the composite process, the heterojunction formed by g-C3N5 and Bi2SiO5 and the presence of nitrogen and oxygen divacancies increase the active sites, improve the light response range of the Bi2SiO5 material, and enable the redox reaction to proceed with higher efficiency.

[0032] The composite material has a high photocurrent density and has a better ability to generate and transport photogenerated carriers, which is beneficial to improving the photocatalytic performance of the catalyst. The composite material has a small impedance arc radius, has a higher photogenerated charge transfer efficiency, the fastest, and the smallest charge transfer resistance, thus having a higher photocatalytic reaction rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1a XRD patterns of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios; Figure 1b for Figure 1a Partially enlarged views of XRD patterns of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios;

[0034] Figure 2a This is the transmission scanning image of Bi2SiO5 / g-C3N5. Figure 2b for Figure 1a A partial enlarged view of the transmission scan of Bi2SiO5 / g-C3N5;

[0035] Figure 3 This is the EDS spectrum of Bi2SiO5 / g-C3N5;

[0036] Figure 4a This is the mapping diagram after all elements of Bi2SiO5 / g-C3N5 are integrated; Figure 4b It is the Bi element mapping image; Figure 4c It is an N-element Mapping image; Figure 4d Mapping image for C element; Figure 4e Mapping image for O element; Figure 4f It is the Si element mapping image;

[0037] Figure 5a UV-visible spectra of Bi2SiO5, g-C3N5, and composite materials of Bi2SiO5 / g-C3N5 with different mass ratios; Figure 5b Bandgap width diagrams of Bi2SiO5, g-C3N5, and composite materials of Bi2SiO5 / g-C3N5 with different mass ratios;

[0038] Figure 6 PL spectra of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios;

[0039] Figure 7a The photocurrent spectra of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios; Figure 7b The optical impedance spectroscopy (EIS) spectra of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios;

[0040] Figure 8a This is the full spectrum of X-ray photoelectron spectroscopy (XPS) of Bi2SiO5 / g-C3N5 composite material; Figure 8b This is the XPS C1s spectrum of Bi2SiO5 / g-C3N5 composite material; Figure 8c This is the N1s spectrum of the Bi2SiO5 / g-C3N5 composite material XPS; Figure 8dThis is the O1s spectrum of the Bi2SiO5 / g-C3N5 composite material XPS; Figure 8e Bi 4f spectrum of Bi2SiO5 / g-C3N5 composite material XPS; Figure 8f is the Si 2p spectrum of the Bi2SiO5 / g-C3N5 composite material XPS;

[0041] Fig. 9 FTIR spectra of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios;

[0042] Fig.10a The degradation diagrams of Rhodamine B by Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios; Fig.10b The kinetic curves of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different mass ratios to Rhodamine B;

[0043] Fig.11 The degradation diagram of RhB with different catalyst amounts;

[0044] Fig.12 The degradation diagram of RhB at different pH values;

[0045] Fig.13a This is the material stability test analysis diagram; Fig.13b is the XRD pattern of the catalyst before and after catalysis;

[0046] Fig.14 It is the mechanism experiment curve diagram;

[0047] Fig.15a Mott-Schottky curve of Bi2SiO5; Fig.15b Mott-Schottky curve of g-C3N5; Fig.15c Mott-Schottky curve of Bi2SiO5 / g-C3N5;

[0048] Fig.16a This is the degradation diagram of ciprofloxacin dye by the catalyst; Fig.16b This is the degradation rate diagram of ciprofloxacin by catalyst. DETAILED DESCRIPTION

[0049] Example 1. Synthesis and characterization of Bi2SiO5 / g-C3N5 composite material

[0050] 1. Synthesis method of Bi2SiO5 / g-C3N5 composite material

[0051] (1) Preparation of Bi2SiO5:

[0052] The preparation method of the bismuth salt solution is as follows: 1.94 g of bismuth nitrate pentahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) are added into a beaker, covered with plastic wrap, and subjected to constant temperature ultrasonic treatment for 30 minutes to obtain a bismuth salt solution;

[0053] The preparation method of the sodium silicate solution is as follows: 0.57 g of sodium silicate nonahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) are mixed and stirred uniformly to obtain a sodium silicate solution.

[0054] Slowly add the sodium silicate solution to the bismuth salt solution, adjust the pH of the solution to 10.0 with a 2 mol / L NaOH solution, and after the reaction is complete, cover with plastic wrap and stir at a constant temperature for 30 mL to obtain a milky white suspension;

[0055] The milky white suspension was transferred to a polytetrafluoroethylene reactor, reacted at 120°C for 12 hours, naturally cooled to room temperature, filtered under reduced pressure, washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 8 hours. The dried material was poured into a clean mortar and ground to obtain white Bi2SiO5 material.

[0056] (2) Synthesis of g-C3N5:

[0057] Place 1.5 g of 3-amino-1,2,4-triazole and 30 mL of deionized water in a beaker and stir to fully dissolve them. Then transfer the beaker to a constant temperature heated magnetic stirrer at 80 °C. After the solution in the beaker is evaporated to dryness, transfer it to a tube furnace and heat it to 520 °C at 5 °C / min. Keep it at 520 °C for 3 hours. After the tube furnace cools to room temperature, take out the porcelain boat, pour the material into a mortar and grind it thoroughly to obtain pure g-C3N5.

[0058] (3) Preparation of Bi2SiO5 / g-C3N5 composite materials:

[0059] 0.05 g of hexadecyltrimethylammonium bromide (CTAB), 30 mL of ethylene glycol and g-C3N5 were added to a beaker, and then transferred to an ultrasonic instrument and ultrasonicated for 30 min at a constant temperature to obtain a mixed solution;

[0060] Then 0.3 g Bi2SiO5 was added to the mixed solution, and constant temperature ultrasound was continued for 30 minutes. The mixture was transferred to a magnetic stirrer and vigorously stirred at a constant temperature for 30 minutes. The mixture was then transferred to a polytetrafluoroethylene reactor for hydrothermal reaction and reacted at 150°C for 8 hours. The reactor was naturally cooled to room temperature, filtered, washed three times with methanol and deionized water respectively, and dried at 60°C to obtain a Bi2SiO5 / g-C3N5 composite material catalyst.

[0061] The ratio of g-C3N5 to Bi2SiO5 is 5%:1, 10%:1, 15%:1, that is, 5% g-C3N5 / Bi2SiO5 is obtained. i2 Composite catalysts with different mass ratios of SiO5, 10% g-C3N5 / Bi2SiO5 and 15% g-C3N5 / Bi2SiO5.

[0062] 2. Characterization of Bi2SiO5 / g-C3N5 composites

[0063] The samples were characterized by XRD, SEM, TEM and XPS, as well as photocurrent and impedance.

[0064] 2.1 XRD characterization

[0065] The parameters used for XRD were: Cu target, scanning range of 10-80°, working voltage of 40 kV, and working current of 40 mA.

[0066] like Figure 1a As shown, the XRD patterns of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 with different g-C3N5 addition amounts are shown. Figure 1b for Figure 1a A partial enlarged view of the .

[0067] 2.2 TEM and EDS spectrum analysis

[0068] The parameters used for XRD were: Cu target, scanning range 10-80°, working voltage 40 kV, working current 40 mA. SEM and TEM scanned the surface morphology, where TEM parameters were: acceleration voltage 200 kV, camera length 520 mm, TEM point resolution 0.25 nm, TEM information resolution 0.12 nm.

[0069] TEM can observe the surface characteristics of materials by electron penetration inside the material. Figure 2a and Figure 2b ( Figure 2b for Figure 2a The local enlarged image shows that the Bi2SiO5 material is a nano-microsphere structure distributed in the layered structure of g-C3N5.

[0070] from Figure 3 It can be seen from the EDS energy spectrum that the measured interlayer spacing of ZnO is d=0.274nm, which corresponds to the (020) crystal plane of hexagonal wurtzite Bi2SiO5, which corresponds to the result measured by XRD.

[0071] Figure 4a-4f is the Mapping graph, Figure 3 It can be seen that C, N, O, Bi, and Si elements are Figure 4a-4f The energy spectrum of Figure 4a The particle signals of each element can be observed in the sample, and no other elements are found, indicating that the sample is of high purity.

[0072] Figure 4b-4f This is an element mapping image. The mapping images of the above five elements can be observed, and they are well distributed in the photocatalytic material.

[0073] 2.3 UV-Vis DRS and PL analysis

[0074] The parameters of PL test were as follows: excitation wavelength 325 nm, excitation voltage 900 V. The scanning range of UV-Vis DRS was 200-800 nm.

[0075] Using standard procedures and mathematical calculations, the UV-Vis DRS spectra of Bi2SiO5, g-C3N5, 5% Bi2SiO5 / g-C3N5, 10% Bi2SiO5 / g-C3N5, and 15% Bi2SiO5 / g-C3N5 were plotted as follows: Figure 5a and Figure 5b shown.

[0076] In the visible light region, the absorption bands of the composite materials are broadened, and a steep curve appears in the wavelength region of 375-400nm, such as Figure 5a As shown, this is related to the shift of the semiconductor band gap. Bi2SiO5 has a large light absorption capacity only in the ultraviolet region, which may be due to its large band gap and difficulty in responding to visible light. The composite material has a strong light response absorption capacity in both the ultraviolet and visible regions. After compounding with g-C3N5, the absorption intensity of the composite material in the ultraviolet region is not significantly reduced compared with Bi2SiO5, and its absorption intensity in the visible light range is further improved, broadening its response range in the visible light.

[0077] The calculated spectrum of the bandgap width is obtained through the Kubelka-Munk transformation. Figure 5b As shown, the band gap energy values ​​of g-C3N5, 5% Bi2SiO5 / g-C3N5, 10% Bi2SiO5 / g-C3N5, 15% Bi2SiO5 / g-C3N5, and Bi2SiO5 are 1.78eV, 2.66eV, 2.88eV, 3.08eV, and 3.68eV, respectively. The band gap of Bi2SiO5 / g-C3N5 is smaller than that of Bi2SiO5, because the additional energy states are introduced after the compounding, resulting in a decrease in the band gap width, which reduces the band gap of Bi2SiO5 / g-C3N5.

[0078] The recombination of photogenerated electron-hole pairs generated during photocatalysis can lead to photoluminescence (PL) emission, so PL spectroscopy can be used to study the separation efficiency of photogenerated electron-hole pairs in semiconductors.

[0079] The higher the separation efficiency of photogenerated electron-hole pairs, the longer their lifetime and the longer they participate in the reaction. Therefore, the photocatalytic performance is mainly determined by the recombination rate or lifetime of photogenerated electron-hole pairs.

[0080] Figure 6 The photoluminescence spectra (PL) of g-C3N5, 5% Bi2SiO5 / g-C3N5, 10% Bi2SiO5 / g-C3N5, 15% Bi2SiO5 / g-C3N5, and Bi2SiO5 are shown in Figure 1, where the excitation wavelength is 325nm. Figure 6 It can be seen that at 450nm, the g-C3N5 composite material exhibits strong PL emission, among which the PL intensity of the 10% Bi2SiO5 / g-C3N5 composite material is lower than that of the other groups of data, which indicates that the electron-hole pair recombination rate of 10% Bi2SiO5 / g-C3N5 is lower, the separation efficiency of photogenerated carriers is higher, and the time involved in the reaction is longer, thus having higher photocatalytic activity.

[0081] 2.4 Photocurrent and impedance (EIS) analysis

[0082] The photocurrent and impedance tests used in this study were completed by the CHI660E413922 electrochemical workstation of Shanghai Chenhua Instrument Co., Ltd. The parameters of the photocurrent test were an initial voltage of 0.3V, a sampling interval of 0.1s, and a sampling time of 400s. The parameters of the impedance test were an initial voltage of 0.28V, an amplitude of 0.005, and a period of 2s.

[0083] Photocurrent response and electrochemical impedance spectroscopy (EIS) can demonstrate the separation and migration capabilities of charge carriers in photocatalysts. Generally, a high photocurrent density indicates a better ability to generate and transport photogenerated charge carriers, which is beneficial to improving the photocatalytic performance of the catalyst.

[0084] like Figure 7a As shown in the figure, under the irradiation of a 500W xenon lamp, the photocurrent response of Bi2SiO5 and g-C3N5 is weaker than that of the composite material. This may be because the band gap of Bi2SiO5 is too wide to respond to the excitation of visible light, and the charge transfer resistance between g-C3N5 powder and the electrolyte solution is too large, resulting in a weak photocurrent response.

[0085] EIS testing can provide a deeper understanding of the charge transfer resistance and separation efficiency between the electrolyte and the photoelectrode surface. The radius of the curve in the figure is related to the separation and transfer efficiency of photogenerated carriers. The smaller the radius of the curve, the smaller the charge transfer resistance, which is more conducive to the separation of photogenerated electron-hole pairs and accelerates the photocatalytic reaction rate. Figure 7b The EIS measurement results shown in the figure indicate that the arc radius of Bi2SiO5 and g-C3N5 is larger than that of the composite material, indicating that the composite material has a higher photogenerated charge transfer efficiency, the fastest charge transfer resistance, and thus a higher photocatalytic reaction rate.

[0086] 2.5 X-ray Photoelectron Spectroscopy (XPS) Analysis

[0087] XPS uses the American Thermo Fisher 250Xi X-ray Photoelectron Spectrometer.

[0088] The surface chemical environment of the samples was studied by X-ray photoelectron spectroscopy (XPS) analysis, and the electronic state and chemical composition of the surface elements of the prepared samples were determined by X-ray photoelectron spectroscopy (XPS) analysis. Figure 8a As shown, Bi, Si, O, C and N elements are present in the composite material without any other impurities, indicating that the composite material is successfully prepared.

[0089] Figure 8a It shows that the sp 2 The bonded carbon is represented by the spectra at 284.8 eV and 288.3 eV, respectively. Figure 8c The positions at 398.6 eV, 399.3 eV, and 400.7 eV correspond to C=NC, N-(C)3 bonds, and CNH bonds, and the bond at 398.6 eV is attributed to sp 2 Bonded nitrogen, i.e., sp 2 The characteristic peak of 399.3 eV is attributed to the N-C3 bond formed by the hybrid aromatic nitrogen and C, while the appearance of the characteristic peak of 400.7 eV is due to the excitation of π electrons. Figure 8d From the O1s spectrum, it can be seen that the characteristic peaks of O 1s appear at binding energies of 530.0 eV and 532.4 eV, respectively. The peak of 530.0 eV is characteristic of lattice oxygen atoms, which is composed of Bi-O-Bi bonds, and the peak of 532.4 eV is attributed to external hydroxyl groups or water molecules adsorbed on the surface, indicating that Bi2SiO5 in the composite material exists in the lattice of the composite material. Figure 8e The XPS spectrum of Bi 4f shows that the two main peaks of Bi2SiO5 / g-C3N5 composite are located at 159.1eV (Bi 4f 7 / 2 ) and 164.4eV(Bi4f5 / 2 ), which is mainly composed of the Bi-O bonds in Bi2SiO5, corresponding to the +3 oxidation state of the Bi element. Figure 8f XPS spectrum of Si 2p, with a characteristic peak at 101.6 eV, corresponding to Si 2p 3 / 2 This confirms that the five elements Bi, Si, O, C and N coexist in the Bi2SiO5 / g-C3N5 composite material, and no other substances appear, which is consistent with the XRD conclusion and strengthens the conclusion that the Bi2SiO5 / g-C3N5 composite material was successfully prepared.

[0090] 2.6 FT-IR spectrum analysis

[0091] Depend on Fig. 9 The Fourier transform infrared spectra (FT-IR) of Bi2SiO5, g-C3N5, and Bi2SiO5 / g-C3N5 are shown. Fig. 9 The curves of Bi2SiO5 and Bi2SiO5 / g-C3N5 show that in the range of 750-850cm -1 The absorption band centered at 940-1030cm corresponds to the stretching vibration of Bi-O-Si. -1 The absorption band centered corresponds to (SiO5) 6- The g-C3N5 and Bi2SiO5 / g-C3N5 curves show that the stretching vibration of the g-C3N5 and Bi2SiO5 / g-C3N5 groups is between 3000 and 3400 cm -1 The absorption band centered on the graph corresponds to the stretching vibration peaks of -NH2 and =NH, which are at 1150-1650cm -1 The absorption band in the center corresponds to the stretching vibration of the basic structural unit of g-C3N5 composed of triazole ring and s-triazine ring.

[0092] Example 2: Photocatalytic degradation of RhB by Bi2SiO5 / g-C3N5 composite material.

[0093] 1. Experimental method of photocatalytic degradation of RhB

[0094] The experiment used 40mg / L RhB (Rhodamine B solution) to simulate pollutants, and a 500W xenon lamp to simulate sunlight conditions. The specific steps are: use an electronic analytical balance to weigh 40mg of Bi2SiO5 / g-C3N5 composite material and then slowly pour it into a quartz test tube containing 40mg / L RhB. Transfer it to the photocatalytic instrument and keep it in a dark environment for 30min dark reaction. After the dark reaction is completed, take a sample, turn on the xenon lamp for light reaction, and then take a sample every 15min, for a total of eight times. Then put the centrifuge tube containing the sample liquid into the low-speed centrifuge in the laboratory and centrifuge it at 5000r / min for 5min to completely precipitate the composite material to avoid errors. Use a UV-visible spectrophotometer to measure the absorbance of the supernatant (the wavelength of the spectrophotometer is positioned at the maximum absorption wavelength of Rhodamine B solution, 554nm).

[0095] 2. Exploration of experimental conditions

[0096] 2.1. Degradation analysis of different Bi2SiO5 / g-C3N5 composites

[0097] By using 40mg / L RhB solution to simulate the wastewater from dye industry, Fig.10a It can be seen that the degradation rate of Bi2SiO5 in 105min is 19.57%, and the degradation rate of g-C3N5 is 38.91%, which shows that Bi2SiO5 and g-C3N5 have certain photocatalytic degradation ability under xenon lamp irradiation. The degradation rate of the composite material has been further improved compared with the single material, reaching 99.82%.

[0098] The fitting diagram of the kinetic curve and the first-order kinetic constant k is obtained by the formula ln(C0 / C)=kt Fig.10b ,According to the analysis of this figure, it can be found that all components can be well fitted.

[0099] Fig.10b The kinetic curves of the degradation rate of Rhodamine B solution by g-C3N5, Bi2SiO5, 5% Bi2SiO5 / g-C3N5, 10% Bi2SiO5 / g-C3N5, and 15% Bi2SiO5 / g-C3N5 are shown, and the slopes are 0.00295, 0.00133, 0.0113, 0.01778, and 0.0074, respectively. Among them, the degradation efficiency of 10% Bi2SiO5 / g-C3N5 is the best, which is 13.37 times that of the single Bi2SiO5 material and 6.02 times that of the g-C3N5 material. This is because in the composite process, the heterojunction formed by g-C3N5 and Bi2SiO5 and the presence of nitrogen and oxygen divacancies increase the active sites, improve the light response range of the Bi2SiO5 material, and make the redox reaction proceed with higher efficiency.

[0100] 2.2 Degradation analysis of different dosages of Bi2SiO5-g-C3N5 composites

[0101] The effect of different catalyst dosages on the degradation rate of Rhodamine B (RhB) solution was determined. Fig.11 It can be seen that under the condition of xenon lamp irradiation, the degradation rates of 0mg, 10mg, 20mg, 30mg, 40mg and 50mg catalysts for rhodamine B are 16.31%, 66.13%, 87.92%, 89.51%, 99.82% and 92.17% respectively. The experiment proves that the best degradation rate is achieved under the condition of 40mg catalyst, which is significantly different from other catalyst dosages, and has better photocatalytic degradation performance than other catalyst dosages. This may be because when the catalyst is less, the photogenerated electron-hole pairs generated by the catalyst after being exposed to light are limited, and it cannot contact with a large number of organic pollutants at the same time, resulting in the oxidation-reduction reaction cannot be carried out in time, so that the degradation efficiency is reduced; when the catalyst is more, the solid powder catalyst will further block the light irradiation, affecting the reaction of the solid powder catalyst with the pollutant, thereby reducing the photocatalytic efficiency.

[0102] 2.3 Effect of different pH on the activity of Bi2SiO5 / g-C3N5 composites

[0103] The effect of different pH on the degradation rate of the catalyst was studied by changing the pH of the Rhodamine B solution. Fig.12 It can be seen that under the conditions of xenon lamp irradiation, the degradation rates of the catalyst for rhodamine B were 59.53%, 69.55%, 98.64%, 42.79% and 28.17% at pH 1, 4, 7, 10 and 14, respectively. The experiment proved that the catalyst had the best degradation rate at pH = 7, and its photocatalytic degradation performance was better than that of other pH values. This is because the change in the pH value of the solution affects the number of hydroxyl groups on the surface of the composite material and the amount of dye rhodamine B adsorbed, thereby affecting the photocatalytic ability. The lower the pH value of the solution, the greater the number of hydroxyl groups on the surface of the composite material, but the composite material particles are positively charged at this time, so the adsorption amount of the cationic dye rhodamine B is reduced; when the pH value of the solution increases to an alkaline environment, the surface charge of the composite material particles becomes negative, thereby reducing the formation of hydroxyl radicals and resulting in a decrease in photocatalytic activity. This may be because in a strong acid or strong base environment, the activity of the catalyst is reduced, and the photogenerated electron-hole pairs generated after being exposed to light are limited, resulting in the inability of the redox reaction to proceed in time, which reduces the degradation efficiency.

[0104] 3. Stability test analysis of Bi2SiO5 / g-C3N5 composite materials

[0105] The cyclic stability of photocatalysts is closely related to whether they can be put into practical application. Therefore, multiple cyclic photocatalytic experiments were carried out on 10% Bi2SiO5 / g-C3N5 composite materials, and the catalyst was recovered by centrifugation after each cycle. Fig.13a The composite material was recycled 5 times, with each reaction lasting 120 minutes. It can be seen that the degradation rate of the catalyst after 5 repeated experiments can still reach 89.93%, without a significant decrease. The reason for the decrease can be attributed to the loss of a small amount of catalyst during each cycle.

[0106] If the experiment is carried out without loss of catalyst, the stability of the 10% Bi2SiO5 / g-C3N5 composite material can be maintained at a high level. Therefore, the Bi2SiO5 / g-C3N5 composite material has great value and practical production potential as a new visible light catalyst. Fig.13b The XRD diagram of the catalyst before and after catalysis shows that the diffraction peaks corresponding to the material before and after catalysis have hardly changed, indicating that the crystal structure properties of the material have not changed before and after catalysis, further proving that the catalyst has good cycle stability.

[0107] 4. Analysis of catalytic mechanism

[0108] The function of the photocatalytic efficiency was evaluated by the effect of different scavengers on the photocatalytic efficiency. Isopropyl alcohol (IPA), disodium ethylenediaminetetraacetate (EDTA-2Na), and p-benzoquinone (BQ) were used to remove hydroxyl radicals (·OH), holes (h + ) and superoxide radicals (·O2 - ) to inhibit. Fig.14 As shown in the figure, in the presence of isopropyl alcohol (IPA), the composite material has almost no effect on the degradation efficiency of RhB, indicating that isopropyl alcohol (IPA) does not have a good inhibitory effect on ·OH, which further indicates that ·OH contributes little to photodegradation. Similarly, in the presence of p-benzoquinone (BQ), the degradation efficiency of the composite material is almost unaffected, indicating that p-benzoquinone (BQ) does not have a good inhibitory effect on (·O2-), which further indicates that (·O2 - ) contributes less to photodegradation. However, when EDTA-2Na is added, the degradation effect of the composite material on rhodamine B (RhB) decreases, indicating that the presence of EDTA-2Na has a good inhibitory effect on holes, indicating that holes contribute more to photodegradation. The results show that h+ is the main active free radical for the composite material to degrade pollutants.

[0109] The determination of the band gap structure is very important for the analysis of the photocatalytic mechanism. In order to further determine the energy band positions of Bi2SiO5, g-C3N5 and Bi2SiO5 / g-C3N5, Mott-Schottky tests were performed on Bi2SiO5, g-C3N5 and Bi2SiO5 / g-C3N5. The results are shown in Figure 2. Figure 15a-Figure 15c As shown. As can be seen from the figure, the slopes of the Mott-Schottky curves of the three catalysts are also positive, indicating that all three are n-type semiconductors, and the flat band potentials of Bi2SiO5, g-C3N5 and Bi2SiO5 / g-C3N5 are 0.09eV, -2.08eV and -2.09eV, respectively. Corresponding to the positions of their conduction bands, combined with the UV-Vis DRS results, the bandgap width of g-C3N5 is 1.78eV, the bandgap width of Bi2SiO5 is 3.68eV, and the bandgap width of Bi2SiO5 / g-C3N5 is 2.88eV. It can be obtained that the valence band position of g-C3N5 is 1.789eV, the valence band position of Bi2SiO5 is 1.60eV, and the valence band position of Bi2SiO5 / g-C3N5 is 0.79eV.

[0110] 5. Degradation of other dyes by catalysts

[0111] The study on the versatility of the catalyst is shown in Figure 16, where Figures (a) and (b) correspond to the degradation of ciprofloxacin and the rate diagram, respectively. It can be seen from the figure that the catalyst also exhibits a strong degradation activity for ciprofloxacin.

[0112] 6. Conclusion of catalytic degradation

[0113] This study elaborated the preparation and properties of Bi2SiO5 / g-C3N5 nanocomposites. The results showed that the degradation rate of the composite material with a composite doping ratio of 10% could reach 98.82% within 120 minutes when the pollutants were simulated by rhodamine B (RhB) solution and sunlight was simulated by xenon lamp. In addition, the experiment proved that the main active factor in the degradation process was h + .

[0114] Example 3

[0115] In this example, the optimal doping ratio of Bi2SiO5 and g-C3N5 obtained in Example 1 and Example 2 was changed to obtain a Bi2SiO5 / g-C3N5 composite material with better catalytic performance. The specific method is as follows:

[0116] Take 1.94 g of bismuth nitrate pentahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) respectively, add them into a beaker, cover with plastic wrap, and perform constant temperature ultrasound for 30 minutes. This mixed solution is recorded as liquid a.

[0117] Take another beaker, add 0.57 g of sodium silicate nonahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) respectively, stir, and this mixed solution is recorded as liquid b.

[0118] Take 1.5 g of 3-amino-1,2,4-triazole (3-AT) and 30 mL of deionized water in a beaker and stir to fully dissolve them. This mixed solution is recorded as liquid C.

[0119] Slowly add liquid c into liquid b and stir evenly. Slowly add the above mixed solution into liquid a, and at the same time adjust the pH of the mixed solution to 10.0 with 2 mol / L NaOH solution. Stir and mix evenly. After complete reaction, cover with plastic wrap and stir at a constant temperature for 30 minutes to obtain a suspension, which is recorded as liquid d.

[0120] Transfer liquid d to a polytetrafluoroethylene reactor, react at 120°C for 12 hours, then evaporate the resulting mixture to dryness at 60-80°C, pour the evaporated material into a clean mortar, and grind it to obtain a composite material precursor.

[0121] The composite material precursor was transferred to a tubular furnace, heated to 520°C at 5°C / min, and kept at 520°C for 3 hours; then an inert gas was introduced, the temperature was raised to 600°C, and the mixture was kept in an inert atmosphere for 5-10 minutes before being naturally cooled. After the tubular furnace cooled to room temperature, the porcelain boat was taken out, the material was poured into a mortar and ground thoroughly to obtain a composite material.

[0122] Compared with the 10% Bi2SiO5 / g-C3N5 composite material catalyst obtained in Example 1 and Example 2, the 10% Bi2SiO5 / g-C3N5 composite material catalyst prepared in this example degrades 40 mg / L RhB solution to simulate dye industry wastewater. Under the same catalyst dosage and other experimental conditions, the time required for the RhB degradation rate to reach more than 99% is shortened by about 53%. This may be because the preparation method of this embodiment is to generate g-C3N5 in situ on the surface of Bi2SiO5, which effectively solves the problem of easy agglomeration and poor dispersibility of g-C3N5, so that g-C3N5 and Bi2SiO5 in the composite material are very evenly dispersed, and g-C3N5 / Bi2SiO5 with smaller particle size, larger specific surface area and higher reaction activity is obtained; the temperature is raised to 600°C in an inert atmosphere environment, so that g-C3N5 tends to sublimate and volatilize, and the microscopic dispersion uniformity of g-C3N5 on the surface of Bi2SiO5 can be deeply adjusted, so that the same amount of g-C3N5 can form more heterojunctions with Bi2SiO5, increase the active sites in the g-C3N5 / Bi2SiO5 material, and thus the final Bi2SiO5 / g-C3N5 composite material has better catalytic performance.

[0123] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A method for synthesizing a Bi2SiO5 / g-C3N5 composite material, characterized in that: The steps include: (1) adding bismuth salt, deionized water and hexadecyltrimethylammonium bromide into a reaction container respectively, and obtaining a mixture after ultrasonic treatment, which is recorded as liquid a; (2) adding silicate, deionized water and hexadecyltrimethylammonium bromide into a reaction container respectively, and stirring to obtain a mixture, which is recorded as liquid B; (3) adding 3-amino-1,2,4-triazole and deionized water into a reaction container respectively, and stirring to obtain a mixture, which is marked as liquid C; (4) First, liquid a and liquid b are mixed and reacted to prepare Bi2SiO5, then liquid c is used to prepare g-C3N5, and finally Bi2SiO5 and g-C3N5 are reacted to prepare Bi2SiO5 / g-C3N5 composite material; or liquid a, liquid b and liquid c are directly mixed and reacted to prepare Bi2SiO5 / g-C3N5 composite material.

2. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to claim 1, characterized in that: In step (1), the preparation method of liquid a is as follows: bismuth nitrate pentahydrate, deionized water, and hexadecyltrimethylammonium bromide (CTAB) are added into a beaker, covered with plastic wrap, and subjected to constant temperature ultrasound to obtain liquid a; In step (2), the preparation method of liquid B is: sodium silicate nonahydrate, deionized water and cetyltrimethylammonium bromide (CTAB) are mixed and stirred evenly to obtain liquid B.

3. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to claim 2, characterized in that: In step (1), the preparation method of liquid a is as follows: 1.94 g of bismuth nitrate pentahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) are added to a beaker, covered with plastic wrap, and subjected to constant temperature ultrasonication for 30 min to obtain liquid a; In step (2), the preparation method of liquid b is as follows: 0.57 g of sodium silicate nonahydrate, 10 mL of deionized water and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) are mixed and stirred evenly to obtain liquid b.

4. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to any one of claims 1 to 3, characterized in that: Slowly add liquid B into liquid A, adjust the pH of the solution with NaOH solution, cover with plastic wrap after complete reaction, and stir at constant temperature to obtain a milky white suspension; The milky white suspension was transferred to a polytetrafluoroethylene reactor, reacted at high temperature, naturally cooled to room temperature, filtered under reduced pressure, washed three times with anhydrous ethanol and deionized water respectively, and then dried. The dried material was poured into a clean mortar and ground to obtain white Bi2SiO5 material.

5. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to claim 4, characterized in that: Slowly add liquid b into liquid a, adjust the pH of the solution to 10.0 with 2 mol / L NaOH solution, cover with plastic wrap after complete reaction, and stir at constant temperature for 30 mL to obtain a milky white suspension; The milky white suspension was transferred to a polytetrafluoroethylene reactor, reacted at 120°C for 12 hours, naturally cooled to room temperature, filtered under reduced pressure, washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 8 hours. The dried material was poured into a clean mortar and ground to obtain white Bi2SiO5 material.

6. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to any one of claims 1 to 3, characterized in that: Place 3-amino-1,2,4-triazole and deionized water in a beaker and stir to fully dissolve them. Then transfer the beaker to a constant temperature heated magnetic stirrer. After the solution in the beaker is evaporated to dryness, transfer it to a tube furnace for heating reaction. After the tube furnace cools to room temperature, take out the porcelain boat, pour the material into a mortar and grind it thoroughly to obtain a material that is pure g-C3N5.

7. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to claim 6, characterized in that: Place 1.5 g of 3-amino-1,2,4-triazole and 30 mL of deionized water in a beaker and stir to fully dissolve them. Then transfer the beaker to a constant temperature heated magnetic stirrer at 80 °C. After the solution in the beaker is evaporated to dryness, transfer it to a tube furnace and heat it to 520 °C at 5 °C / min. Keep it at 520 °C for 3 hours. After the tube furnace cools to room temperature, take out the porcelain boat, pour the material into a mortar and grind it thoroughly to obtain pure g-C3N5.

8. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to any one of claims 1 to 3, characterized in that: Add hexadecyltrimethylammonium bromide (CTAB), ethylene glycol and g-C3N5 into a beaker, and then transfer to an ultrasonic instrument and perform constant temperature ultrasonication to obtain a mixed solution; Then Bi2SiO5 was added to the mixed solution, and after continued constant temperature ultrasound, it was transferred to a magnetic stirrer. After constant temperature and vigorous stirring, it was transferred to a polytetrafluoroethylene reactor for hydrothermal reaction. After the reactor was naturally cooled to room temperature, it was filtered, washed with methanol and deionized water, and dried to obtain a Bi2SiO5 / g-C3N5 composite material.

9. The method for synthesizing the Bi2SiO5 / g-C3N5 composite material according to any one of claims 1 to 3, characterized in that: Slowly add liquid C to liquid B, stir evenly, then slowly add to liquid A, stir and mix evenly, and adjust the pH of the mixed solution to alkaline with NaOH solution. After the reaction is complete, stir to obtain a suspension, which is recorded as liquid D; The d liquid is transferred to a polytetrafluoroethylene reactor for hydrothermal reaction, and then the obtained mixture is evaporated to dryness, and the solid obtained after evaporation is ground to obtain a composite material precursor; the composite material precursor is transferred to a tubular furnace for heating and reaction, and after the tubular furnace is cooled to room temperature after the reaction, it is taken out and ground to obtain a Bi2SiO5 / g-C3N5 composite material.

10. Use of Bi2SiO5-g-C3N5 composite material, characterized in that: The Bi2SiO5 / g-C3N5 composite material described in any one of claims 1 to 9 is used for photocatalytic degradation of organic pollutants.

Citation Information

Patent Citations

  • Flowerlike bismuth silicate / bismuth molybdate heterojunction photocatalyst, and preparation method and application thereof

    CN111013569A

  • Preparation method and application of efficient Bi4O5Br2 / g-C3N5 composite photocatalytic material

    CN115212906A

  • Method for manufacturing metal-filled microstructure

    WO2021176847A1

Cited By

  • AuAg-loaded bimetallic Ag2Mo2O7 / g-C3N5 composite material as well as preparation method and application thereof

    CN120268460A